Non Performing Financing (Npf) In Islamic Banking In Indonesia - Zulfahmi Syahputra Nasution; Nurul Atika Fitri Nasution (EKOMBIS REVIEW: Jurnal Ilmiah Ekonomi dan Bisnis, 2024)
Data on non-performing financing (NPF) or non-performing funding is known to vary, and the six Islamic banks surveyed were declared healthy in the funding category. The purpose of this study is to determine the NPF situation in Islamic banking in Indonesia from 2010 to 2016. This study uses secondary data in the form of financial statements of each Islamic Bank which are tested based on overall NPF performance. An increase in NPF funding, among others, will change the level of ROA. The highest NPF data is 3.78% and the lowest is 2.18%.